The effect of point-of-care ultrasound on length of stay and mortality in patients with chest pain/dyspnea - Huang, Chien-Tai; Chang, Chih-Heng; Chen, Jia-Yu; Ling, Dean-An; Lee, An-Fu; Wang, Pei-Hsiu; Wu, Chien-Kai; Ko, Ying-Chih; Hsiao, Yu-Tse; Lien, Wan-Ching; Chang, Wei-Tien; Huang, Chien-Hua (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Purpose This study aims to investigate the effects of point-of-care ultrasound (PoCUS) on length of stay (LOS) and mortality in hemodynamically stable patients with chest pain/dyspnea.Materials and Methods The prospective study was conducted from June 2020 to May 2021. A convenience sample of adult non-traumatic patients with chest pain/dyspnea was included and evaluated by PoCUS. The primary outcome was the relationship between the door-to-PoCUS time and LOS/mortality categorized by the ST-segment elevation (STE) and non-STE on the initial electrocardiogram. The diagnostic accuracy of PoCUS was computed, compared to the final diagnosis.Results A total of 465 patients were included. 3 of 18 patients with STE had unexpected cardiac tamponade and 1 had myocarditis with pulmonary edema. PoCUS had a minimal effect on LOS and mortality in patients with STE. In the non-STE group, the shorter door-to-PoCUS time was associated with a shorter LOS (coefficient, 1.26±0.47, p=0.008). After categorizing the timing of PoCUS as 30, 60, 90, and 120 minutes, PoCUS had a positive effect, especially when performed within 90 minutes of arrival, on LOS of less than 360 minutes (OR, 2.42, 95% CI, 1.61–3.64) and patient survival (OR, 3.32, 95% CI, 1.14–9.71). The overall diagnostic performance of PoCUS was 96.6% (95% CI, 94.9–98.2%), but lower efficacy occurred in pulmonary embolism and myocardial infarction.Conclusion The use of PoCUS was associated with a shorter LOS and less mortality in patients with non-STE, especially when performed within 90 minutes of arrival. Although the effect on patients with STE was minimal, PoCUS played a role in discovering unexpected diagnoses.
Keywords: Point of care; Echocardiography; Chest